SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN PORANG (Amorphophallus muelleri B.) DENGAN PELARUT EKSTRAKSI ETANOL, ETIL ASETAT DAN N-HEKSANA - Ni Putu Febri Suryani; I Putu Gede Adi Purwa Hita; I Gusti Ayu Agung Septiari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Free radicals are molecules that are unstable and highly reactive because they have one or more unpaired electrons. Antioxidants are compounds that can inhibit oxidation reactions by binding to free radicals and highly reactive molecules. Antioxidants can be obtained in synthetic and natural forms. Due to the disadvantages of synthetic antioxidants, the research interest in natural antioxidant is growing. One of the plants that can be studied as a natural antioxidant is the porang plant (Amorphophallus muelleri Blume) which is a type of plant that has potential both technologically and commercially in terms of medical, industrial and food. The selection of solvents with different polarities will affect the extraction results, so in this study extraction solvents with different polarities were used with the aim of knowing the content of secondary metabolites and antioxidant activity contained in porang leaf extract (Amorphophallus muelleri Blume) with 96% ethanol, ethyl acetate and n-hexane. To determine the content of secondary metabolites and antioxidant activity in different solvents of porang (Amorphophallus muelleri Blume) leaf extract with 96% ethanol, ethyl acetate and n-hexane. Antioxidant activity test using the DPPH (2,2-diphenyl-1-picrylhydrazil) method was measured using Spectrophotometry UV-Vis at a maximum wavelength of 516 nm. The value of IC50 of porang leaf extract in ethanol, ethyl acetate, and n-hexane respectively 100 ppm (strong), 131.54 ppm (moderate), and 215.39 ppm (very weak). In conclucion, the three porang leaf extracts with different solvents had antioxidant activity with different category.